EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN FAN-N-PICK PADA PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KECEMASAN PADA MATEMATIKA SISWA SMP NEGERI DI KABUPATEN MAGELANG - Setyowati, Anna; Budiyono, Budiyono; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from the studentâs mathematics anxiety. The learning model compared were Teams Games Tournament of cooperative learning model, Fan-N-Pick of coopeartive learning model, and direct instruction model The method which was applied in this research was quasi-experimental with 3Ã3 factorial design done in class VIII second semester of Junior High School (SMP) In Magelang Regency Academic Year 2012/2013. Sampling technique using stratified cluster random sampling. The research concludes as follows. 1) Fan-N-Pick of cooperative learning model gave better mathematics learning achievement than TGT of cooperative learning model and direct instructional model. While, TGT of cooperative learning model gave betterÂ mathematics learning achievement than direct instructional model. 2) The students with low levels of mathematics anxiety had mathematics learning achievement is better than students with medium and high of mathematics anxiety. While students with medium levels of mathematics anxiety had mathematics learning achievement is better than students with high levels of mathematics anxiety. 3) In the TGT of cooperative learning model, students with high and medium levels of mathematics anxiety had similar good mathematics achievement. So also students with medium and low levels of mathematics anxiety had similar good mathematics achievement. However, the TGT of cooperative learning model, students with low levels of mathematics anxiety had mathematics learning achievement is better than students with high levels of mathematics anxiety. In the Fan-N-Pick of cooperative learning model, students with low, medium and high levels of mathematics anxiety had similar good mathematics achievement. In the direct instructional model, students with low levels of mathematics anxiety had mathematics learning achievement is better than students with medium and high of mathematics anxiety. 4) On students with low levels of mathematics anxiety by using TGT and Fan-N-Pick of cooperative learning model and direct instructional model had similar good mathematics achievement. Students with medium and high levels of mathematics anxiety, mathematics achievement had equally well if given a model of learning through direct instruction model and TGT of cooperative learning model. Likewise if given learning with TGT and Fan-N-Pick of cooperative learning model had similar good mathematics achievement. However, students with medium and high levels of mathematics anxiety had better mathematics achievement through Fan-N-Pick of cooperative learning model rather than through direct instructional model. Key words: Teams Games Tournament (TGT), Fan-N-Pick, Mathematics Anxiety